Language variation and language change across the lifespan theoretical and empirical perspectives from panel studies - Beaman, Karen V.; Buchstaller, Isabelle (Routledge studies in language change, 2021)
"This volume brings together research on panel studies with the aim of providing a coherent empirical and theoretical knowledge-base for examining the impact of maturation and lifespan-specific effects on linguistic malleability in the post-adolescent speaker. Building on the work of Wagner and Buchstaller (2017), the present collection offers a critical examination of the theoretical implications of panel research across a range of geographic regions and time periods. The volume seeks to offer a way forward in the debates circling about the phenomenon of later-life language change, drawing on contributions from a variety of linguistic disciplines to examine critical topics such as the effect of linguistic architecture, the roles of mobility and identity construction, and the impact of frequency effects. Taken together, this edited collection both informs and pushes forward key questions on the nature of lifespan change, making this key reading for students and researchers in cognitive linguistics, historical linguistics, dialectology, and variationist sociolinguistics"--